Telemedicine Enables Broader Access to Movement Disorders Curricula for Medical Students. (19th October 2017) - Cubo, Esther; Doumbe, Jacques; López, Emiliano; Lopez, Guadalupe A.; Gatto, Emilia; Persi, Gabriel; Guttman, Mark
Background: The impact of tele-education for movement disorders on medical students is unknown. The present study had three objectives. First, to create a tele-education program for medical students in regions with limited access to movement disorders curricula. Second, to analyze the feasibility, satisfaction, and improvement of medical knowledge. Third, to assess the main reasons of medical students for attending this course. Methods: In 2016, a program was piloted in a low-middle income (Cameroon) and a middle-high income (Argentina) country. Medical students were offered a free movement disorder tele-education program (four medical schools in Argentina, and 1 medical school in Cameroon). Six real-time videoconferences covering hyperkinetic and hypokinetic movement disorders were included. Evaluations included attendance, pre- and post-medical knowledge, and satisfaction questionnaires. Results: The study included 151 undergraduate medical students (79.4% from Argentina, 20.6% from Cameroon). Feasibility was acceptable with 100% and 85.7% of the videoconferences completed in Argentina and Cameroon, respectively. Attendance was higher in Argentina compared to Cameroon (75% vs. 33.1%). According to student reports, the topics and innovative educational environment were the main reasons for attendance. Both groups ranked satisfaction as moderate to high, and medical knowledge improved similarly in both countries. Discussion: Tele-education can improve movement disorders knowledge in medical schools in high-middle and low-middle income countries lacking access to other educational opportunities.